Effect of pH on lactic acid fermentation of food waste using different mixed culture inocula. Issue 4 (1st December 2021) - Pau, Simone; Tan, Lea Chua; Lens, Piet NL
Abstract: BACKGROUND: Increasing amounts of food waste (FW) have become a critical problem in the last few decades. Sustainable methods to limit the impact of FW on the environment are required. FW valorisation through lactic acid (LA) fermentation can assist by producing a valuable commodity from a cheap substrate. LA is a chemical with increasing market potential, it is used in several industrial sectors, and it is the main component of polylactic acid bioproducts. RESULTS: The role of pH on LA production from FW was tested with three anaerobic inocula and a control with solely FW. The most suitable condition for LA production was at pH < 4. The best results in terms of final LA concentration (1.8 gCOD L –1 ), yield (224 mgCOD/gVS), and COD conversion (50%) were found in uncontrolled pH conditions with no external inoculum addition. FW already has a good abundance of LA bacteria that are responsible for lactate production. Among the external inocula supplied, primary sludge best enabled LA accumulation at a high concentration (1.3 g COD L –1 ) and yield (167 mgCOD/gVS). CONCLUSION: This study demonstrates that the reactor pH is a key factor to stimulate LA acid fermentation and its accumulation. Under acidic conditions, LA accumulated in the system instead of being converted to volatile fatty acids (VFAs); this was likely due to the inhibition of the microbial community responsible for VFAs production. Uncontrolled pH condition impacts positively the overall fermentation cost since the alkalinizing agents used to keep pH neutral are not required and simplifies the downstream processes for LA extraction and purification. © 2021 Society of Chemical Industry (SCI).